Reviews. (1st June 2014) - Amos, Will; Blin-Rolland, Armelle; McCusker, Maeve; Martinon, Jean-Paul; Miraglia, Anne-Marie; Small, Audrey; Smith, Alison
L'Algérie et la langue française ou l'altérité en partage, Rabeh Sebaa (2013) Paris: Publibook, 104 pp., ISBN: 9782342007404, p/bk, €14Redrawing French Empire in Comics, Mark McKinney (2013) Columbus: The Ohio State University Press, 288 pp., ISBN: 1397808142122202, h/bk, 79.95Caribbean Literature and the Public Sphere. From the Plantation to the Postcolonial, Raphael Dalleo (2011) Charlottesville and London: University of Virginia Press, 296 pp., ISBN: 9780813931999, P/bk, £26.50V. Y. Mudimbe: Undisciplined Africanism, Pierre-Philippe Fraiture (2013) Liverpool: Liverpool University Press, 260 pp., ISBN: 9781846318948, h/bk, £67.94Vers l'imaginaire migrant. La Fiction narrative des écrivains immigrants francophones au Québec (1980–2000), Tina Mouneimné (2013) Bruxelles: P.I.E. Peter Lang, 207 pp., ISBN: 9782875740328, p/bk, £29Postcolonial Thought in the French-speaking World, Charles Forsdick and David Murphy (eds) (2009) Liverpool: Liverpool University Press, 357 pp., ISBN-1: 9781846310546, h/bk, £65, ISBN-2: 9781846310553, p/bk, £19.95Contesting Views: The Visual Economy of France and Algeria, Edward Welch and Joseph McGonagle (2013) Liverpool: Liverpool University Press, 236 pp., ISBN: 9781846318849, h/bk